Response of bacterioplankton to iron fertilization of the Southern Ocean, Antarctica - Singh, Sanjay Kumar; Kotakonda, Arunasri; Kapardar, Raj Kishor; Kankipati, Hara Kishore; Pasupuleti, Sreenivasa Rao; Mambatta, Pratibha S.; Vetaikorumagan, Sundareswaran R.; Gundlapally, Sathyanarayana Reddy; Nagappa, Ramaiah; Shivaji, Sisinthy (Frontiers in Microbiology, 2015)
Ocean iron fertilization is an approach to increase CO2 sequestration. The Indo-German iron fertilization experiment “LOHAFEX” was carried out in the Southern Ocean surrounding Antarctica in 2009 to monitor changes in bacterial community structure following iron fertilization-induced phytoplankton bloom of the seawater from different depths. 16S rRNA gene libraries were constructed using metagenomic DNA from seawater prior to and after iron fertilization and the clones were sequenced for identification of the major bacterial groups present and for phylogenetic analyses. A total of 4439 clones of 16S rRNA genes from ten 16S rRNA gene libraries were sequenced. More than 97.35% of the sequences represented four bacterial lineages i.e. Alphaproteobacteria, Gammaproteobacteria, Bacteroidetes and Firmicutes and confirmed their role in scavenging of phytoplankton blooms induced following iron fertilization. The present study demonstrates the response of Firmicutes due to Iron fertilization which was not observed in previous southern ocean Iron fertilization studies. In addition, this study identifies three unique phylogenetic clusters LOHAFEX Cluster 1 (affiliated to Bacteroidetes), 2 and 3 (affiliated to Firmicutes) which were not detected in any of the earlier studies on iron fertilization. The relative abundance of these clusters in response to iron fertilization was different. The increase in abundance of LOHAFEX Cluster 2 and Papillibacter sp. another dominant Firmicutes may imply a role in phytoplankton degradation. Disappearance of LOHAFEX Cluster 3 and other bacterial genera after iron fertilization may imply conditions not conducive for their survival. It is hypothesised that heterotrophic bacterial abundance in the Southern Ocean would depend on their ability to utilise algal exudates, decaying algal biomass and other nutrients thus resulting in a dynamic bacterial succession of distinct genera.